Infectious complications of mine-explosive trauma: etiology of wound infections and principles of antimicrobial therapy (literature review) - D. A. Prokopovich; L. V. Lagun; D. A. Yakovlenko (Military Medicine, 2026)
Infectious complications remain the leading cause of mortality and prolonged hospitalisation in military personnel sustaining mine-explosive trauma (MET). The aim of this study was to analyse the current spectrum of infectious complications of MET, evaluate the aetiological structure of wound pathogens, and determine rational principles of antimicrobial prophylaxis and therapy. A systematic review of 18 scientific publications from 2012–2025 was performed. Infectious complications were found to develop in 27–35 % of combat casualties and in 52 % of those sustaining traumatic amputations. In contemporary conflicts, the dominant pathogens are multidrug-resistant Gram-negative bacteria– Acinetobacter baumannii, Klebsiellapneumoniae, and Pseudomonas aeruginosa – with carbapenem resistance rates reaching 73–90 %. The cornerstone of antimicrobial prophylaxis remains prompt cefazolin administration per TCCC protocol; radical wound debridement is essential for infection prevention. The spread of multidrug-resistant organisms from conflict zones constitutes a global epidemiological threat.